THE DEVELOPMENT AND VALIDATION OF SCIENCE VIRTUAL TEST TO ASSESS 7TH GRADE STUDENTS' CRITICAL THINKING ON MATTER AND HEAT TOPIC, 2017 - Sya'bandari, Yustika (2017)
An efficient way to improve the quality of education in critical thinking is developing the better tests. The test has been shifted towards the use of computer-based procedures. Lack of specific topic of critical thinking tests in science and the advanced of technology made the researcher intended to develop and validate a test to measure students' critical thinking in the matter and heat topic based on computer for seventh grade junior high school. Generally, the process of developing and validating the test consists of 5 steps: (1) content analysis; (2) constructing multiple choice items; (3) readability test and expert validation; (4) limited tryout; and (5) larger application. Based on larger application, it is obtained the reliability value, difficulty level, discriminating power and distractor quality. The method that used in this research was descriptive. The subject was 117 students of public Junior High School in Kabupaten Bandung. The instrument validation resulted 30 items that represent 8 elements and 21 sub-elements to measure students' critical thinking based on Inch in matter and heat topic. The instrument is further called as Science Virtual Test Matter and Heat (SVT-MH). The alpha Cronbach (α) is 0.642 which means that the instrument is sufficient to measure students' critical thinking matter and heat topic. The result also shows the profile of students in critical thinking is 73% categorized as 'moderate', while students respond the positive impression towards the use of SVT-MH, Keywords: Science virtual test, critical thinking, matter and heat, readability test, validity, reliability, students' impression. Cara yang efisien untuk meningkatkan kualitas pendidikan dalam berpikir kritis adalah membuat tes yang lebih baik. Prosedur tes telah beralih menggunakan komputer. Kurangnya tes berpikir kritis dalam topik spesifik sains dan kemajuan teknologi membuat peneliti mengembangkan dan memvalidasi tes untuk mengukur kemampuan berfikir kritis siswa dalam topik klasifikasi zat dan kalor berbasis computer untuk kelas tujuh Sekolah Menengah Pertama. Secara umum, pengembangan dan validasi tes terdiri dari lima tahap: (1) analisis materi; (2) pembuatan soal pilihan ganda; (3) uji keterbacaan dan validasi ahli; (4) uji coba terbatas; dan (5) Aplikasi skala besar. Berdasarkan aplikasi pada skala yang lebih besar, diperoleh nilai reliabilitas, tingkat kesukaran, daya pembeda dan kualitas distraktor. Metode yang digunakan dalam penelitian ini adalah deskriptif. Subjek yaitu 117 siswa Sekolah Menengah Pertama Negeri di Kabupaten Bandung. Validasi instrumen menghasilkan 30 soal yang mewakili 8 elemen dan 21 sub-elemen untuk mengukur kemampuan berfikir kritis siswa berdasarkan Inch dalam topi klasifikasi zat dan kalor. Instrumen ini selanjutnya disebut Science Virtual Test Matter and Heat (SVT-MH). Alpha Cronbach (α) sebesar 0,642 yang berarti instrumen tersebut cukup untuk mengukur kemampuan berfkir kritis siswa dalam topik klasifikasi zat dan kalor. Hasil juga menunjukkan bahwa profil siswa dalam berpikir kritis adalah 73% dikategorikan 'moderat', sementara siswa merespon positif terhadap penggunaan SVT-MH, Kata kunci: Science virtual test, berfikir kritis, klasifikasi zat dan kalor, uji keterbacaan, validitas, reliabilitas, impresi siswa,